1995
DOI: 10.1037/1040-3590.7.2.140
|View full text |Cite
|
Sign up to set email alerts
|

Racial differences in adolescent self-report: A comparative validity study using homogeneous MMPI content measures.

Abstract: MMPIs) were administered to an urban-mixedrace sample of adolescent psychiatric inp'atients and outpatients (N = 218). Racial differences were noted on 4 of the 13 raw Wiggins scale scores, with scores for African-American patients more elevated on Poor Health, Feminine Interests, Phobias, and Psychoticism. A backward multiple-regression procedure was used to predict raw Wiggins scale scores from parent descriptions as measured by the Personality Inventory for Children clinical scales. Predictors supported the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

1998
1998
2011
2011

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Similarly, Knight et al (1994) reported that correlations between measures of depression, anxiety, and conduct disorder were equivalent in samples of White and Hispanic youths. Wrobel and Lachar (1995), however, reported that depression was more highly correlated with anxiety among White youths than among Black youths and that depression was more highly correlated with family problems, delinquency, hyperactivity, and psychosis among Black youths than among White youths.…”
mentioning
confidence: 90%
See 2 more Smart Citations
“…Similarly, Knight et al (1994) reported that correlations between measures of depression, anxiety, and conduct disorder were equivalent in samples of White and Hispanic youths. Wrobel and Lachar (1995), however, reported that depression was more highly correlated with anxiety among White youths than among Black youths and that depression was more highly correlated with family problems, delinquency, hyperactivity, and psychosis among Black youths than among White youths.…”
mentioning
confidence: 90%
“…Of these studies, two reported that Black youths scored higher on depression measures than did White youths (Garrison, Jackson, Marsteller, McKeown, & Addy, 1990;Mc-Donald & Gynther, 1963). Five studies found no significant differences between Black and White youth on measures of depression (Helsel & Matson, 1984;Lubin & McCollum, 1994;Reynold & Graves, 1989;Treadwell, Flannery-Schroeder, & Kendall, 1995;Wrobel & Lachar, 1995). One study revealed that White youths scored higher than Black youths.…”
mentioning
confidence: 99%
See 1 more Smart Citation